Key influencers of puberty knowledge among Indonesian adolescents: the role of social networks - Sulistiawan, Dedik; Arifa, Riza Fatma; Matahari, Ratu; Dirgantara, Syariatul; Chakranon, Pairote (International Journal of Public Health Science (IJPHS), 2025)
Accurate reproductive health knowledge is essential for adolescents, yet many in Indonesia poorly informed, contributing to risky behaviors. While prior studies have focused on the effectiveness of reproductive health promotion media, limited research has explored the role of social networks in shaping adolescent reproductive health knowledge. This study aimed to investigate the key influencers within adolescents' social networks by analyzing the association between discussion partners on sexuality and knowledge of puberty-related traits. This cross-sectional study utilized data from the 2017 Indonesia Demographic and Health Survey, with a sample of 23,361 unmarried adolescents. We assessed knowledge of puberty onset traits and discussion partners on sexuality issues as predictors. Multiple logistic regression, adjusted for age, gender, wealth index, and residence, was employed to calculate odds ratios with 95% confidence intervals. Approximately half of the adolescents demonstrated a good knowledge of puberty-related traits. Engaging in discussions about sexuality with friends, mothers, relatives, teachers, and health professionals was positively associated with higher knowledge levels. Adolescents who engaged with these sources were more likely to have a better understanding of puberty-related traits. Utilizing key influencers within these networks can be crucial in promoting accurate reproductive health knowledge and reducing risky behaviors in this population.